About STEM from the Perspective of STS - Poviliūnas, Arūnas (Acta Paedagogica Vilnensia, 2019)
The movement of STEM has become the synonym for the renewal of science education. Nevertheless, the movement of STEM is not unambiguous. The article discusses two contradicting interpretations of STEM. The first one descends from the Weltanschauung of Modernity, the second one – from the critics of Modernity. According to the former, STEM education deals with the purification and integration of the disciplines of science education and answers the needs of the high-tech labour market. The latter one emphasizes the syncretic and anthropological character of the ecological mind and the changing patterns of consumption and production in favour of sustainable development. This version of STEM is closely related to the development of STS, which paves the way from purification and integration to the translation and human and non-human networking (ANT). The article searches for the answer to the question of how to deal with the confronting STEM versions in the process of the renewal of science education.